2019
DOI: 10.1002/er.4678
|View full text |Cite
|
Sign up to set email alerts
|

Morphology‐dependent electrochemical performance of nitrogen‐doped carbon dots@polyaniline hybrids for supercapacitors

Abstract: Summary In this work, the binary N‐CDs@PANI hybrids were fabricated by introducing zero‐dimensional nitrogen‐doped carbon dots (N‐CDs) into reticulated PANI. Firstly, N‐CDs were prepared by one‐pot microwave method, and then, the N‐CDs were introduced into in situ oxidative polymerization of aniline (ANI) monomer. The N‐CDs with abundant functional groups and high electronic cloud density played a significant role in guiding the polyaniline‐ordered growth into intriguing morphologies. Moreover, morphology‐depe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 52 publications
4
30
0
Order By: Relevance
“…23 Currently, the most widely used electrode materials in EDLCs are activated carbons (ACs), which generally possess high surface area, good electric conductivity, and excellent long-term cycling stability. 22,[24][25][26] Heteroatoms doping [27][28][29][30][31] or co-doping [32][33][34][35] can effectively improve the energy storage of ACs, and the dependence of the chargestorage capability of ACs on the surface area of ACs has stimulated the interest to fabricate porous ACs to increase specific adsorption sites. 5 However, the topology of ACs is another important factor likely controlling the migration of electrolyte ions during electrochemical cycling.…”
Section: Introductionmentioning
confidence: 99%
“…23 Currently, the most widely used electrode materials in EDLCs are activated carbons (ACs), which generally possess high surface area, good electric conductivity, and excellent long-term cycling stability. 22,[24][25][26] Heteroatoms doping [27][28][29][30][31] or co-doping [32][33][34][35] can effectively improve the energy storage of ACs, and the dependence of the chargestorage capability of ACs on the surface area of ACs has stimulated the interest to fabricate porous ACs to increase specific adsorption sites. 5 However, the topology of ACs is another important factor likely controlling the migration of electrolyte ions during electrochemical cycling.…”
Section: Introductionmentioning
confidence: 99%
“…The NMR spectra and FTIR spectra identify the surface chemical groups on as‐obtained CDs shown in Figure S1. These active functional groups on the surface of CDs would improve the hydrophilicity of CDs, which is helpful for promoting the contact between the electrode material and the electrolyte . As‐synthesized CDs with a lattice spacing of 0.215 nm and the average diameter is around 7 to 12 nm.…”
Section: Resultsmentioning
confidence: 99%
“…45 Zhaofen et al has reported a specific capacitance of 160.5 F/g for aniline-grafting graphene oxide/PANI (GO-ANI/PANI) composite. 47 We have taken acetylene black as a carbon source to reduce the cost and prepared a new ternary composite (polyaniline-acetylene blackcopper cobaltite). 47 We have taken acetylene black as a carbon source to reduce the cost and prepared a new ternary composite (polyaniline-acetylene blackcopper cobaltite).…”
Section: Figurementioning
confidence: 99%
“…46 Recently, Fei et al has prepared nitrogen-doped carbon dots@polyaniline hybrids, and the reported specific capacitance value is 785 F/g. 47 We have taken acetylene black as a carbon source to reduce the cost and prepared a new ternary composite (polyaniline-acetylene blackcopper cobaltite).…”
Section: Figurementioning
confidence: 99%